2005
DOI: 10.1063/1.1944220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic dilution in Zn1−xMnxGa2Se4 (0<x<0.5)

Abstract: The profound effect of magnetic dilution in Zn 1−x Mn x Ga 2 Se 4 with 0 Ͻ x Ͻ 0. 5 is demonstrated by the analysis of neutron powder diffraction and magnetic susceptibility data. All the members of the series show a defective stannite crystal structure and a random distribution of the Mn ions. The magnetic archetype system of Zn 1−x Mn x Ga 2 Se 4 with 0 Ͻ x Ͻ 0. 5 is not found to be MnGa 2 Se 4 ͑the magnetic end member of the series with I4 symmetry͒ but, instead, a hypothetical compound with I42m symmetry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…Room temperature parameters obtained in this work are in good agreement with [12] and [13] The dependence of a, c and σ with temperature and composition is attributed to the combined effect of thermal expansion and changes in the degree of structural order, both at the phase transition and before. For chalcopyrite materials it has been shown that anisotropic thermal expansion occurs, yielding in general an increase of the tetragonal distortion with temperature [31].…”
Section: Neutron Diffractionsupporting
confidence: 80%
See 2 more Smart Citations
“…Room temperature parameters obtained in this work are in good agreement with [12] and [13] The dependence of a, c and σ with temperature and composition is attributed to the combined effect of thermal expansion and changes in the degree of structural order, both at the phase transition and before. For chalcopyrite materials it has been shown that anisotropic thermal expansion occurs, yielding in general an increase of the tetragonal distortion with temperature [31].…”
Section: Neutron Diffractionsupporting
confidence: 80%
“…As regards the Zn 1-x Mn x Ga 2 Se 4 series, electronic band gap and magnetic properties have been shown to vary non-monotonically with composition [9][10][11], a fact that has been attributed to a varying degree of disorder along the series. This hypothesis has been verified in a structural study performed by means of time of flight (TOF) neutron diffraction at room temperature (RT) [10][11][12][13]. As reported in [10], the degree of order is closely related to the Mn occupancy of the available sites: 2d and 2c (if the space group is I-4) or 4d (if it is I- Mn partially occupies the 2d and 2c sites, resulting in 0< η <1.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…This is in contrast with the nearly constant value of c detected in Zn 1−x Mn x Ga 2 Se 4 with 0 ഛ x Ͻ 0.5, which exhibit a completely random distribution of the Zn cations. 25 The increase of c / a with decreasing x suggests a tendency to an increase in cation ordering as the concentration of Mn progresses. 26 This conclusion also agrees with the distribution of the magnetic ions determined for Zn 1−x Mn x Ga 2 Se 4 with 0.5Ͻ x ഛ 1 ͑see Table I͒.…”
Section: -2mentioning
confidence: 99%
“…Following that law, 1 / =− / C + T / C, the agreement between the slope 1 / C calculated from both diffraction and magnetic data has been used as a criterion to support the choice of temperature range used for the fitting of the magnetic data and, as a consequence, the reliability of the resultant values. 25 The Curie constant C can be calculated from the diffraction data using the Mn content obtained from such data, x diff , and the mathematical expression of C, which is a function of x ͑see above͒. The results for are shown in Table II.…”
Section: B Magnetic Behaviormentioning
confidence: 99%